ANALISIS YURIDIS PENYELESAIAN SENGKETA ROYALTI MUSIK MELALUI MEKANISME NON-LITIGASI (STUDI KASUS MIE GACOAN DI INDONESIA) - Rizki Rizki; Yasmin Az Zahra; Mhd Raihan Fawwaz Husni (Jurnal Ilmiah Advokasi, 2026)
This study aims to analyze the settlement of music royalty disputes in Indonesia with particular emphasis on non-litigation mechanisms, especially in cases involving the restaurant chain Mie Gacoan. Disputes concerning music royalties have increased in line with the growing commercial use of musical works without authorization or adequate payment to copyright holders. This research employs a normative juridical method with statutory, conceptual, and case-based approaches. The theoretical framework is grounded in the Theory of Legal Protection, the Theory of Justice, and the Theory of Legal Certainty. The findings indicate that dispute settlement through non-litigation mechanisms, such as mediation and negotiation facilitated by Collective Management Organizations (LMK) and the National Collective Management Organization (LMKN), in practice accelerates resolution without the need for judicial adjudication. One of the study’s observations shows that mediation processes conducted by LMKN in several similar cases including cases with patterns comparable to the Mie Gacoan dispute successfully reached royalty payment agreements in a shorter time than litigation, while simultaneously reducing dispute costs and preserving business relations between the parties. In the Mie Gacoan case, the dispute arose from the use of music within the commercial area of the restaurant chain without authorization from the copyright holders. The dispute was subsequently reported to LMKN and resolved through non-litigation procedures in the form of negotiation and mediation, which resulted in an agreement on royalty payment without recourse to judicial proceedings. This case study demonstrates that non-litigation mechanisms function as a strategic instrument for enforcing justice and legal protection for creators, while at the same time providing legal certainty for business operators.Keywords: Copyright, Music Royalty, Dispute, Non-Litigation